Teoria da Cegueira Deliberada e a sua (in)aplicabilidade no ordenamento jurídico brasileiro - Lopes, Alexandre Ribeiro (2024)
The text discusses the Theory of Deliberate Blindness and its application in Brazilian Criminal Law. This theory, widely recognized in Common Law systems, is foreign to the Civil Law system adopted in Brazil, which traditionally requires proof of intent or guilt to commit crimes. Despite accepted by jurisprudence and doctrine in specific cases, is not confirmed in constitutional norms or infraconstitutional provisions of the country. Willful Blindness introduces a subjective perspective, in which the agent deliberately refrains from recognizing the illegality of their actions. This raises questions about your compatibility with Brazilian constitutional principles, such as the presumption of innocence and the principle of legality. The theory was recently incorporated into the Brazilian legal system, in 2005, generating debates about its applicability and legitimacy. The study proposes a reflection on the import of this theory into a predominantly Civil Law legal system and highlights the need for judicial solutions when the law does not offers clear answers for specific cases.